Salt response hyperbranched polymer filtrate reducer as well as preparation method and application thereof
Through the introduction of the salt response of the ucchic and cationic groups in the polymer reduction loss agent, the problem of the polymer filtration loss agent chain in the high -salt environment is solved, and the high temperature, high mineralization and the degree of high mineralization and high mineralization Stable filtration loss effect in high salt environment.
Patent Information
- Application Number
- CN202411510524.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
AI Technical Summary
The existing polymer filter reduction agents are unable to maintain effective performance in high-salt environments due to the charge shielding of ions, resulting in molecular chains curling and losing their effect in high-temperature, high mineralization and high-priced salt environments.
The salt response hyperplastic polymer reduction loss agent is used. The material is used to introduce anion and cationic groups by introducing anion and cationic groups to avoid molecular chains in a high -salt environment and maintain a good filtration loss effect.
In high temperature (> 200 ° C), high mineralization (> 100000 mg/L) and high -salt environment, the salt response hyperdigical polymer filtrate loss agent can maintain good drilling fluid flow and filtration and loss. Stablize.
Smart Images

Figure BDA0005105327050000301 
Figure BDA0005105327050000311 
Figure BDA0005105327050000321
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield drilling fluid fluid loss reducers, and in particular to a salt-responsive hyperbranched polymer fluid loss reducer and a preparation method and application thereof. Background Art
[0002] Drilling fluid is called the "blood" of drilling engineering, and its performance is related to the success or failure of drilling operations. As one of the core additives, the main function of fluid loss reducer is to form a thin and dense mud cake on the well wall under the action of pressure difference, preventing filtrate or solid particles from invading the formation, thereby achieving the purpose of stabilizing the well wall and protecting the reservoir. With the development of the global oil and gas industry, the exploration and development of oil and gas has shifted from shallow layers to deep and ultra-deep layers. In addition, salt-gypsum layers are widely distributed underground. When drilling into such formations, the contact between drilling fluid and salt-gypsum layers in the formation is inevitable. Therefore, the harsh geological characteristics of deep wells and ultra-deep wells, such as high temperature (>200℃), high pressure (>140MPa) and high mineralization (>100000mg / L), pose higher challenges to the performance of fluid loss reducers.
[0003] Fluid loss reducers are mainly divided into two categories: natural polymers and synthetic polymers. Natural polymers cannot meet the requirements of fluid loss reduction in deep and ultra-deep well drilling due to easy degradation under high temperature conditions. Instead, synthetic polymers are used. Most of these polymers are polyacrylamide and its derivatives. In order to solve the problem that synthetic polymers degrade at high temperatures and cause the performance of fluid loss reducers to fail, domestic and foreign scholars usually use methods such as introducing temperature-resistant monomers into polymers, adjusting the ratio between monomer components, and controlling molecular weight to deal with it. Although these methods effectively improve the temperature resistance of polymer fluid loss reducers, and the molecular chains of fluid loss reducers can be fully stretched in fresh water to exert their effects, polymers are polyelectrolytes. In the presence of salt, their molecular chains will curl up through electrostatic attraction, reducing the solubility of the fluid loss reducer or even making it insoluble, and finally causing it to lose its effect. Especially for environments with high mineralization and high-price salt, the performance of polymer fluid loss reducers cannot be guaranteed.
[0004] Therefore, it is necessary to develop a high temperature resistant (>200°C) and high mineralization (>100,000 mg / L) water-based drilling fluid filtrate reducer suitable for deep wells and ultra-deep wells. Summary of the invention
[0005] The purpose of the present invention is to overcome the problem that the polymer fluid loss reducer in the prior art has poor salt resistance due to the charge shielding effect of ions, which weakens the electrostatic force on the charged groups of the polymer and makes the molecular chains of the polymer unable to stretch, thereby providing a salt-responsive hyperbranched polymer fluid loss reducer and a preparation method and application thereof. The salt-responsive hyperbranched polymer fluid loss reducer provided by the present invention has a hyperbranched structure, and a core unit is constituted by a polyene monomer. By introducing anionic and cationic groups into the hyperbranched structure, the molecular chain curling phenomenon caused by the "polyelectrolyte effect" of the polymer in a high-salt environment can be avoided, so that the polymer still has a good fluid loss reduction effect in an environment with a high concentration of metal salt ions, and can be used for ultra-deep oil and gas drilling.
[0006] In order to achieve the above object, the present invention provides a salt-responsive hyperbranched polymer fluid loss reducer on one hand, wherein the salt-responsive hyperbranched polymer fluid loss reducer comprises:
[0007] The first structural unit is provided by an unsaturated amide water-soluble monomer;
[0008] The second structural unit is provided by an unsaturated cationic water-soluble monomer;
[0009] The third structural unit is provided by an unsaturated anionic water-soluble monomer;
[0010] The fourth structural unit is provided by a polyene monomer;
[0011] Wherein, the weight average molecular weight of the salt-responsive hyperbranched polymer fluid loss reducer is 20,000 to 100,000.
[0012] Preferably, the weight ratio of the first structural unit, the second structural unit, the third structural unit and the fourth structural unit is (3-30):(1.6-20):(1.6-20):1, preferably (5-15):(3-8):(3-8):1.
[0013] Preferably, the unsaturated amide water-soluble monomer is at least one of acrylamide, N-isopropylacrylamide, methacrylamide and N,N-dimethylacrylamide.
[0014] Preferably, the unsaturated cationic water-soluble monomer is at least one of dimethyldiallylammonium chloride, (3-acrylamidopropyl)trimethylammonium chloride, methacryloyloxyethyltrimethylammonium chloride and allyltrimethylammonium chloride.
[0015] Preferably, the unsaturated anionic water-soluble monomer is at least one of sodium 2-acrylamide-2-methylpropane sulfonate, sodium methacrylic acid sulfonate, sodium allyl sulfonate and sodium styrene sulfonate.
[0016] Preferably, the polyolefin monomer is at least one of pentaerythritol triallyl ether, trimethylolpropane triallyl ether, triallylamine and triallylcarbinol.
[0017] The second aspect of the present invention provides a method for preparing a salt-responsive hyperbranched polymer fluid loss reducer, the method comprising the following steps:
[0018] (1) mixing an unsaturated amide water-soluble monomer with water to obtain a first solution;
[0019] (2) reacting the first solution obtained in step (1) with a polyene monomer in the presence of a first initiator under an inert atmosphere;
[0020] (3) mixing an unsaturated cationic water-soluble monomer and an unsaturated anionic water-soluble monomer with water to obtain a second solution;
[0021] (4) subjecting the second solution obtained in step (3) to a secondary reaction with the reaction product obtained in step (2) in the presence of a second initiator.
[0022] Preferably, the weight ratio of the total amount of the unsaturated amide water-soluble monomer, the unsaturated cationic water-soluble monomer, the unsaturated anionic water-soluble monomer and the polyolefin monomer, the first initiator and the second initiator to water is (3-30): (1.6-20): (1.6-20): 1: (0.01-0.2): (14-200), preferably (5-15): (3-8): (3-8): 1: (0.05-0.15): (20-180).
[0023] Preferably, the unsaturated amide water-soluble monomer is at least one of acrylamide, N-isopropylacrylamide, methacrylamide and N,N-dimethylacrylamide.
[0024] Preferably, the unsaturated cationic water-soluble monomer is at least one of dimethyldiallylammonium chloride, (3-acrylamidopropyl)trimethylammonium chloride, methacryloyloxyethyltrimethylammonium chloride and allyltrimethylammonium chloride.
[0025] Preferably, the unsaturated anionic water-soluble monomer is at least one of sodium 2-acrylamide-2-methylpropane sulfonate, sodium methacrylic acid sulfonate, sodium allyl sulfonate and sodium styrene sulfonate.
[0026] Preferably, the polyolefin monomer is at least one of pentaerythritol triallyl ether, trimethylolpropane triallyl ether, triallylamine and triallylcarbinol.
[0027] Preferably, in step (1), the mass ratio of the unsaturated amide water-soluble monomer to water is 1:(1-5), preferably 1:(2-4).
[0028] Preferably, in step (2), the first initiator is used in the form of an aqueous solution, and the concentration of the aqueous solution of the first initiator is 0.005-0.02 g / mL, preferably 0.006-0.015 g / mL.
[0029] Preferably, in step (2), the primary reaction is carried out under stirring, and the conditions of the primary reaction include: a temperature of 35-45° C. and a stirring speed of 300-1000 r / min.
[0030] Preferably, in step (3), the mass ratio of the total amount of the unsaturated cationic water-soluble monomer and the unsaturated anionic water-soluble monomer to water is 1:(0.5-1.5), preferably 1:(0.8-1.2).
[0031] Preferably, the first initiator is ammonium persulfate and / or sodium bisulfite.
[0032] Preferably, in step (4), the secondary reaction time is 2-3 hours.
[0033] The third aspect of the present invention provides a drilling fluid, which contains the salt-responsive hyperbranched polymer fluid loss reducer as described above.
[0034] The salt-responsive hyperbranched polymer fluid loss reducer of the present invention is obtained by copolymerizing unsaturated amide water-soluble monomers, unsaturated cationic water-soluble monomers, unsaturated anionic water-soluble monomers and polyolefin monomers. When used in water-based drilling fluid, it can maintain good drilling fluid rheology and fluid loss reduction performance under high temperature (>200°C) and high mineralization (>100000 mg / L) conditions and is stable for a long time. DETAILED DESCRIPTION
[0035] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0036] The salt-responsive hyperbranched polymer fluid loss reducer of the present invention comprises a first structural unit, a second structural unit, a third structural unit and a fourth structural unit, wherein the first structural unit is provided by an unsaturated amide water-soluble monomer, the second structural unit is provided by an unsaturated cationic water-soluble monomer, the third structural unit is provided by an unsaturated anionic water-soluble monomer, and the fourth structural unit is provided by a polyene monomer. According to the salt-responsive hyperbranched polymer fluid loss reducer of the present invention, by combining the four types of structural units, the fluid loss reducer can maintain good drilling fluid rheology and fluid loss performance in a high temperature and high salt environment, and is stable for a long time when used in a water-based drilling fluid.
[0037] In the salt-responsive hyperbranched polymer fluid loss reducer of the present invention, the weight ratio of the first structural unit, the second structural unit, the third structural unit and the fourth structural unit can be (3-30): (1.6-20): (1.6-20): 1, preferably (5-15): (3-8): (3-8): 1. When the ratio of the four types of structural units in the salt-responsive hyperbranched polymer fluid loss reducer is within the above range (especially the preferred range), the salt-responsive hyperbranched polymer fluid loss reducer has better fluid loss reduction performance.
[0038] In the present invention, the weight average molecular weight of the salt-responsive hyperbranched polymer fluid loss agent is 20,000 to 100,000, preferably 20,000 to 80,000, and more preferably 30,000 to 60,000. In this article, the weight average molecular weight of the salt-responsive hyperbranched polymer fluid loss agent is obtained by gel permeation chromatography.
[0039] In the present invention, the unsaturated amide water-soluble monomer can be at least one of acrylamide, N-isopropylacrylamide, methacrylamide and N,N-dimethylacrylamide. In the most preferred embodiment, the unsaturated amide water-soluble monomer is acrylamide. When the unsaturated amide water-soluble monomer adopts the above preferred embodiment, the salt-responsive hyperbranched polymer fluid loss reducer has better fluid loss reduction performance.
[0040] In the present invention, the unsaturated cationic water-soluble monomer can be at least one of dimethyldiallylammonium chloride, (3-acrylamidopropyl)trimethylammonium chloride, methacryloyloxyethyltrimethylammonium chloride and allyltrimethylammonium chloride. In the most preferred embodiment, the unsaturated cationic water-soluble monomer is allyltrimethylammonium chloride. When the unsaturated cationic water-soluble monomer adopts the above preferred embodiment, the salt-responsive hyperbranched polymer fluid loss reducer has better fluid loss reduction performance.
[0041] In the present invention, the unsaturated anionic water-soluble monomer can be at least one of sodium 2-acrylamide-2-methylpropane sulfonate, sodium methacrylate sulfonate, sodium allyl sulfonate and sodium styrene sulfonate. In the most preferred embodiment, the unsaturated anionic water-soluble monomer is sodium methacrylate sulfonate. When the unsaturated anionic water-soluble monomer adopts the above preferred embodiment, the salt-responsive hyperbranched polymer fluid loss reducer has better fluid loss reduction performance.
[0042] In the present invention, the polyolefin monomer can be at least one of pentaerythritol triallyl ether, trimethylolpropane triallyl ether, triallylamine and triallyl carbinol. In the most preferred embodiment, the polyolefin monomer is triallyl carbinol. When the polyolefin monomer adopts the above preferred embodiment, the salt-responsive hyperbranched polymer fluid loss reducer has better fluid loss reduction performance.
[0043] The preparation method of the salt-responsive hyperbranched polymer fluid loss reducer of the present invention comprises the following steps:
[0044] (1) mixing an unsaturated amide water-soluble monomer with water to obtain a first solution;
[0045] (2) reacting the first solution obtained in step (1) with a polyene monomer in the presence of a first initiator under an inert atmosphere;
[0046] (3) mixing an unsaturated cationic water-soluble monomer and an unsaturated anionic water-soluble monomer with water to obtain a second solution;
[0047] (4) subjecting the second solution obtained in step (3) to a secondary reaction with the reaction product obtained in step (2) in the presence of a second initiator.
[0048] In the method of the present invention, the weight ratio of the total amount of the unsaturated amide water-soluble monomer, the unsaturated cationic water-soluble monomer, the unsaturated anionic water-soluble monomer and the polyolefin monomer, the first initiator and the second initiator to water can be (3-30): (1.6-20): (1.6-20): 1: (0.01-0.2): (14-200), preferably (5-15): (3-8): (3-8): 1: (0.05-0.15): (20-180). The salt-responsive hyperbranched polymer fluid loss reducer prepared according to the above ratio range (especially the preferred range) has better fluid loss reduction performance.
[0049] In the method of the present invention, the conditions of the primary reaction and the secondary reaction are such that the weight average molecular weight of the prepared salt-responsive hyperbranched polymer fluid loss reducer is 20,000 to 100,000, preferably 20,000 to 80,000, and more preferably 30,000 to 60,000.
[0050] In the method of the present invention, the unsaturated amide water-soluble monomer can be at least one of acrylamide, N-isopropylacrylamide, methacrylamide and N,N-dimethylacrylamide. In the most preferred embodiment, the unsaturated amide water-soluble monomer is acrylamide. Under the above preferred conditions, the prepared salt-responsive hyperbranched polymer fluid loss reducer has better fluid loss reduction performance.
[0051] In the method of the present invention, the unsaturated cationic water-soluble monomer can be at least one of dimethyldiallylammonium chloride, (3-acrylamidopropyl)trimethylammonium chloride, methacryloyloxyethyltrimethylammonium chloride and allyltrimethylammonium chloride. In the most preferred embodiment, the unsaturated cationic water-soluble monomer is allyltrimethylammonium chloride. When the unsaturated cationic water-soluble monomer adopts the above preferred embodiment, the prepared salt-responsive hyperbranched polymer fluid loss reducer has better fluid loss reduction performance.
[0052] In the method of the present invention, the unsaturated anionic water-soluble monomer can be at least one of sodium 2-acrylamide-2-methylpropane sulfonate, sodium methacrylate sulfonate, sodium allyl sulfonate and sodium styrene sulfonate. In the most preferred embodiment, the unsaturated anionic water-soluble monomer is sodium methacrylate sulfonate. When the unsaturated anionic water-soluble monomer adopts the above preferred embodiment, the prepared salt-responsive hyperbranched polymer fluid loss reducer has better fluid loss reduction performance.
[0053] In the method of the present invention, the polyolefin monomer can be at least one of pentaerythritol triallyl ether, trimethylolpropane triallyl ether, triallylamine and triallyl carbinol. In the most preferred embodiment, the polyolefin monomer is pentaerythritol triallyl ether. When the polyolefin monomer adopts the above preferred embodiment, the prepared salt-responsive hyperbranched polymer fluid loss reducer has better fluid loss reduction performance.
[0054] In step (1), the mass ratio of the unsaturated amide water-soluble monomer to water can be 1: (1-5), preferably 1: (2-4), specifically, for example, 1: 2, 1: 2.2, 1: 2.5, 1: 2.8, 1: 3, 1: 3.2, 1: 3.5, 1: 3.8 or 1: 4. The salt-responsive hyperbranched polymer fluid loss reducer formed under this preferred condition has significantly higher fluid loss reduction performance.
[0055] In step (2), the first initiator is used in the form of an aqueous solution, and the concentration of the aqueous solution of the first initiator can be 0.005-0.02 g / mL, preferably 0.006-0.015 g / mL, specifically, for example, 0.006 g / mL, 0.007 g / mL, 0.008 g / mL, 0.009 g / mL, 0.01 g / mL, 0.011 g / mL, 0.012 g / mL, 0.013 g / mL, 0.014 g / mL or 0.015 g / mL. The salt-responsive hyperbranched polymer fluid loss reducer prepared under this preferred condition has significantly higher fluid loss reduction performance.
[0056] In step (2), the primary reaction is carried out under stirring. The conditions of the primary reaction may include: a temperature of 35-45° C. and a stirring speed of 300-1000 r / min. In a more preferred case, the conditions of the primary reaction may include: a temperature of 36-43° C. and a stirring speed of 400-800 r / min. The salt-responsive hyperbranched polymer fluid loss reducer prepared under this preferred condition has significantly higher fluid loss reduction performance.
[0057] In step (2), the inert atmosphere can be provided by at least one of nitrogen, helium and argon. In the most preferred embodiment, the inert atmosphere can be provided by nitrogen.
[0058] In step (3), the mass ratio of the total amount of the unsaturated cationic water-soluble monomer and the unsaturated anionic water-soluble monomer to water can be 1:(0.5-1.5), preferably 1:(0.8-1.2).
[0059] In the method of the present invention, the first initiator can be ammonium persulfate and / or sodium bisulfite. In the most preferred embodiment, the initiator is a combination of sodium persulfate and sodium bisulfite, and the mass ratio of sodium persulfate to sodium bisulfite is (1-3):1, preferably (1.2-3):1. In the above preferred case, the salt-responsive hyperbranched polymer fluid loss reducer has better fluid loss reduction performance.
[0060] In the method of the present invention, the second initiator can be ammonium persulfate and / or sodium bisulfite. In the most preferred embodiment, the initiator is a combination of sodium persulfate and sodium bisulfite, and the mass ratio of sodium persulfate to sodium bisulfite is (1-3):1, preferably (1.2-3):1. In the above preferred case, the salt-responsive hyperbranched polymer fluid loss reducer has better fluid loss reduction performance.
[0061] In the method of the present invention, the second initiator is the same as or different from the first initiator, preferably the same as the first initiator. In the above preferred case, the salt-responsive hyperbranched polymer fluid loss reducer has better fluid loss reduction performance.
[0062] In step (4), the secondary reaction time may be 2-3 hours, preferably 2.2-2.8 hours, specifically, for example, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours or 2.8 hours. In the above preferred case, the salt-responsive hyperbranched polymer fluid loss reducer has better fluid loss reduction performance.
[0063] In step (4), the second solution can be added using a constant pressure funnel, and the addition speed can be 2-5 s / mL, preferably 2-3 s / mL.
[0064] In the method described in the present invention, the preparation method of the salt-responsive hyperbranched polymer filtrate reducer also includes: purifying the product obtained by the secondary reaction with ethanol, and then drying and crushing. The product obtained by the secondary reaction can be a gel-like substance. The drying conditions can include: a temperature of 60-80°C and a time of 20-30h. The drying process can be implemented in various conventional ovens in the art. The crushing conditions can include: a rotation speed of 15000-30000r / min and a crushing time of 20-60s. The crushing process can be implemented in various conventional crushers in the art. The salt-responsive hyperbranched polymer filtrate reducer can be a white powder after drying and crushing.
[0065] The drilling fluid of the present invention contains a fluid loss reducer, and the fluid loss reducer is a salt-responsive hyperbranched polymer fluid loss reducer provided by the present invention. The drilling fluid of the present invention can maintain good drilling fluid rheology and fluid loss reduction performance under high temperature (>200°C) and high salinity (>100000 mg / L) conditions, and is stable for a long time.
[0066] The salt-responsive hyperbranched polymer fluid loss reducer and its preparation method and application described in the present invention are further illustrated by examples. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.
[0067] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0068] In the following examples and comparative examples, the performance of the salt-responsive hyperbranched polymer fluid loss reducer was tested according to the following method:
[0069] Plastic viscosity test: Use a direct-reading viscometer for testing. Inject the sample into the sample cup to the scale line, place the sample on the viscometer base, and move the base so that the sample liquid level coincides with the scale line on the outer cylinder. Rotate the outer cylinder at 600r / min, and after the dial reading stabilizes, record the dial reading R 600 . Change the speed to 300r / min, wait for the dial reading to stabilize, and record the dial reading R 300 Calculate the plastic viscosity η p , the unit is milliPascal seconds (centipoise).
[0070] η p =R 600 -R 300
[0071] Where:
[0072] R 600 —Dial reading at 600r / min;
[0073] R 300 —Dial reading at 300r / min.
[0074] Apparent viscosity test: Use a direct-reading viscometer for testing. Inject the sample into the sample cup to the scale line, place the sample on the viscometer base, and move the base so that the sample liquid level coincides with the scale line on the outer cylinder. Rotate the outer cylinder at 600r / min, and after the dial reading stabilizes, record the dial reading R 600 Calculate the apparent viscosity η a , the unit is milliPascal seconds (centipoise).
[0075] η a =R 600 / 2
[0076] Where:
[0077] R 600 —Dial reading at 600r / min.
[0078] Dynamic shear force test: Use a direct-reading viscometer for testing. Inject the sample into the sample cup to the scale line, place the sample on the viscometer base, and move the base so that the sample liquid level coincides with the scale line on the outer cylinder. Rotate the outer cylinder at 300r / min, and record the dial reading R after the dial reading stabilizes. 300 , calculate the dynamic shear force Y p , the unit is Pa.
[0079] Y p =0.5×(R 300 -η p )
[0080] Where:
[0081] R 300 —Dial reading at 300r / min;
[0082] η p —Plastic viscosity, mPas (centipoise).
[0083] API filtration test: Use a filter loss meter to test the content. Inject the sample into the drilling fluid cup so that the liquid level is 1-1.5 cm from the top of the drilling fluid cup, then place the filter paper and install the filter loss meter. Place a dry measuring cylinder under the discharge pipe to receive the filtrate. Close the pressure relief valve and adjust the pressure regulator to reach the target pressure in 30 seconds or less. Start timing while pressurizing, and record relevant data after 30 minutes.
[0084] HTHP filtration test: Use a filtration meter to test the content. Stir the sample with a high-speed stirrer for 10 minutes, close the bottom valve, and pour the drilling fluid into the drilling fluid cup. Assemble the drilling fluid cup and close the bottom valve stem, and put it into the heating jacket. Insert the thermometer into the thermometer socket on the drilling fluid cup. Connect the high-pressure filtrate receiver to the bottom valve stem and lock it, and connect the adjustable pressure source to the top valve stem and the bottom filtrate receiver respectively and lock them. Adjust the top and bottom pressure regulators to the target pressure respectively. Open the bottom valve and record the relevant data.
[0085] Example 1
[0086] (1) 10 g acrylamide, 20 g methacrylamide and 90 mL water were added to a reactor. Under stirring, 3 g triallyl carbinol was added to the reaction device, nitrogen was introduced to react, and the stirrer speed was 500 r / min.
[0087] (2) Add 0.07 g of ammonium persulfate to 7 mL of water to obtain an ammonium persulfate solution. Add 0.03 g of ammonium bisulfite to 3 mL of water to obtain an ammonium bisulfite solution. Heat the reaction system obtained in step (1) to 36°C, introduce nitrogen for 30 min, then drop the ammonium persulfate solution into the reaction system, control the drop rate to one drop every 3 seconds, and complete the drop within 3 min; 5 min later, add the sodium bisulfite solution into the reaction system, control the drop rate to one drop every 3 seconds, and complete the drop within 3 min to carry out the reaction, with a stirring rate of 600 r / min.
[0088] (3) 15 g of allyltrimethylammonium chloride and 10 g of sodium methyl propylene sulfonate were added to 20 mL of water to obtain a solution.
[0089] (4) The reaction product obtained in step (2) and the solution obtained in step (3) are loaded into a constant pressure dropping funnel, and slowly added to a reaction bottle, with the dropping speed controlled at one drop per 3 seconds; 0.07 g of ammonium persulfate is added to 7 mL of water to obtain an ammonium persulfate solution; 0.03 g of sodium bisulfite is added to 3 mL of water to obtain an ammonium bisulfite solution; the ammonium persulfate solution is added dropwise to the reaction system, with the dropping speed controlled at one drop per 3 seconds, and the addition is completed within 3 minutes. After 5 minutes, the sodium bisulfite solution is added dropwise to the reaction system, with the dropping speed controlled at one drop per 3 seconds, and the addition is completed within 3 minutes to react. After the reaction is completed, the mixture is naturally cooled to room temperature to obtain a transparent viscous substance.
[0090] (5) The transparent viscous substance obtained in step (5) is purified by anhydrous ethanol and then dried to obtain a white solid. The white powder after crushing is the salt-responsive hyperbranched polymer fluid loss reducer A1 of the present invention.
[0091] (6) 16 g of bentonite and 2.4 g of anhydrous sodium carbonate were added to 400 mL of water, stirred at high speed for 20 min, and cured at room temperature for 24 h to obtain a fresh water base slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A1 of the present invention was mixed with the fresh water base slurry and stirred at high speed for 20 min to obtain a test sample A1-1.
[0092] (7) 44 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A1 of the present invention was mixed with the saltwater slurry to obtain a test sample A1-2.
[0093] (8) 100 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A1 of the present invention was mixed with the saltwater slurry to obtain a test sample A1-3.
[0094] (9) 140 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A1 of the present invention was mixed with the saltwater slurry to obtain a test sample A1-4.
[0095] (10) Test sample A1-1, test sample A1-2, test sample A1-3 and test sample A1-4 obtained in step (6), step (7), step (8) and step (9) are respectively added into an aging tank, and hot-rolled at 220° C. for 16 hours to obtain test sample A1-5, test sample A1-6, test sample A1-7 and test sample A1-8, respectively.
[0096] Test samples A1-1, A1-2, A1-3, A1-4, A1-5, A1-6, A1-7 and A1-8 were subjected to apparent viscosity test, plastic viscosity test, dynamic shear force test, API filtration loss test and HTHP filtration loss test respectively. The results are as follows:
[0097] The apparent viscosity of the test sample A1-1 is 6.5 mPa·s, the plastic viscosity is 5 mPa·s, the dynamic shear force is 1.5 Pa, and the API filtration loss is 8 mL.
[0098] The apparent viscosity of the test sample A1-2 is 8 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 1 Pa, and the API filtration loss is 7.5 mL.
[0099] The apparent viscosity of the test sample A1-3 is 9.5 mPa·s, the plastic viscosity is 9 mPa·s, the dynamic shear force is 0.5 Pa, and the API filtration loss is 6.4 mL.
[0100] The apparent viscosity of the test sample A1-4 is 10 mPa·s, the plastic viscosity is 9 mPa·s, the dynamic shear force is 1 Pa, and the API filtration loss is 6.6 mL.
[0101] The apparent viscosity of the test sample A1-5 is 5.5 mPa·s, the plastic viscosity is 5 mPa·s, the dynamic shear force is 0.5 Pa, the API filtration loss is 8.5 mL, and the HTHP filtration loss is 18.2 mL.
[0102] The apparent viscosity of the test sample A1-6 is 7.5 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 0.5 Pa, the API filtration loss is 7.8 mL, and the HTHP filtration loss is 18.5 mL.
[0103] The apparent viscosity of the test sample A1-7 is 9 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 1 Pa, the API filtration loss is 6.8 mL, and the HTHP filtration loss is 17.8 mL.
[0104] The apparent viscosity of the test sample A1-8 is 10 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 2 Pa, the API filtration loss is 6.2 mL, and the HTHP filtration loss is 17.5 mL.
[0105] Example 2
[0106] (1) 5 g of acrylamide, 10 g of methacrylamide and 60 mL of water were added to a reactor. Under stirring, 3 g of triallyl carbinol was added to the reaction device, nitrogen was introduced to react, and the stirrer speed was 500 r / min.
[0107] (2) Add 0.05 g of ammonium persulfate to 7 mL of water to obtain an ammonium persulfate solution. Add 0.02 g of ammonium bisulfite to 3 mL of water to obtain an ammonium bisulfite solution. Heat the reaction system obtained in step (1) to 40°C, introduce nitrogen for 30 min, then drop the ammonium persulfate solution into the reaction system, control the drop rate to one drop every 3 seconds, and complete the drop within 3 min; 5 min later, drop the sodium bisulfite solution into the reaction system, control the drop rate to one drop every 3 seconds, and complete the drop within 3 min to carry out the reaction, with a stirring rate of 400 r / min.
[0108] (3) 9 g of allyltrimethylammonium chloride and 9 g of sodium methyl propylene sulfonate were added to 20 mL of water to obtain a solution.
[0109] (4) The reaction product obtained in step (2) and the solution obtained in step (3) are loaded into a constant pressure dropping funnel and slowly added to a reaction bottle, with the dropping speed controlled at one drop per 3 seconds; 0.06 g of ammonium persulfate is added to 7 mL of water to obtain an ammonium persulfate solution; 0.02 g of sodium bisulfite is added to 3 mL of water to obtain an ammonium bisulfite solution; the ammonium persulfate solution is added dropwise to the reaction system, with the dropping speed controlled at one drop per 3 seconds, and the addition is completed within 3 minutes. After 5 minutes, the sodium bisulfite solution is added dropwise to the reaction system, with the dropping speed controlled at one drop per 3 seconds, and the addition is completed within 3 minutes to react. After the reaction is completed, the mixture is naturally cooled to room temperature to obtain a transparent viscous substance.
[0110] (5) The transparent viscous substance obtained in step (5) is purified by anhydrous ethanol and then dried to obtain a white solid. The white powder after crushing is the salt-responsive hyperbranched polymer fluid loss reducer A2 of the present invention.
[0111] (6) 16 g of bentonite and 2.4 g of anhydrous sodium carbonate were added to 400 mL of water, stirred at high speed for 20 min, and cured at room temperature for 24 h to obtain a fresh water base slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A2 of the present invention was mixed with the fresh water base slurry and stirred at high speed for 20 min to obtain a test sample A2-1.
[0112] (7) 44 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A2 of the present invention was mixed with the saltwater slurry to obtain a test sample A2-2.
[0113] (8) 100 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A2 of the present invention was mixed with the saltwater slurry to obtain a test sample A2-3.
[0114] (9) 140 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A2 of the present invention was mixed with the saltwater slurry to obtain a test sample A2-4.
[0115] (10) Test sample A2-1, test sample A2-2, test sample A2-3 and test sample A2-4 obtained in step (6), step (7), step (8) and step (9) are respectively added into an aging tank, and hot-rolled at 220°C for 16 hours to obtain test sample A2-5, test sample A2-6, test sample A2-7 and test sample A2-8, respectively.
[0116] Test samples A2-1, A2-2, A2-3, A2-4, A2-5, A2-6, A2-7 and A2-8 were subjected to apparent viscosity test, plastic viscosity test, dynamic shear force test, API filtration loss test and HTHP filtration loss test respectively. The results are as follows:
[0117] The apparent viscosity of the test sample A2-1 is 6.5 mPa·s, the plastic viscosity is 5 mPa·s, the dynamic shear force is 1.5 Pa, and the API filtration loss is 8.2 mL.
[0118] The apparent viscosity of the test sample A2-2 is 8 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 1 Pa, and the API filtration loss is 7.7 mL.
[0119] The apparent viscosity of the test sample A2-3 is 9.5 mPa·s, the plastic viscosity is 9 mPa·s, the dynamic shear force is 0.5 Pa, and the API filtration loss is 6.5 mL.
[0120] The apparent viscosity of the test sample A2-4 is 10 mPa·s, the plastic viscosity is 9 mPa·s, the dynamic shear force is 1 Pa, and the API filtration loss is 6.6 mL.
[0121] The apparent viscosity of the test sample A2-5 is 5.5 mPa·s, the plastic viscosity is 5 mPa·s, the dynamic shear force is 0.5 Pa, the API filtration loss is 8.9 mL, and the HTHP filtration loss is 18.6 mL.
[0122] The apparent viscosity of the test sample A2-6 is 7.5 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 0.5 Pa, the API filtration loss is 8 mL, and the HTHP filtration loss is 18.7 mL.
[0123] The apparent viscosity of the test sample A2-7 is 9 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 1 Pa, the API filtration loss is 6.9 mL, and the HTHP filtration loss is 18.1 mL.
[0124] The apparent viscosity of the test sample A2-8 is 10 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 2 Pa, the API filtration loss is 6.5 mL, and the HTHP filtration loss is 17.9 mL.
[0125] Example 3
[0126] (1) 15 g acrylamide, 30 g methacrylamide and 90 mL water were added to a reactor. Under stirring, 3 g triallyl carbinol was added to the reaction device, nitrogen was introduced to react, and the stirrer speed was 500 r / min.
[0127] (2) Add 0.08 g of ammonium persulfate to 7 mL of water to obtain an ammonium persulfate solution. Add 0.04 g of ammonium bisulfite to 3 mL of water to obtain an ammonium bisulfite solution. Heat the reaction system obtained in step (1) to 43°C, introduce nitrogen for 30 min, then drop the ammonium persulfate solution into the reaction system, control the drop rate to one drop every 3 seconds, and complete the drop within 3 min; 5 min later, drop the sodium bisulfite solution into the reaction system, control the drop rate to one drop every 3 seconds, and complete the drop within 3 min to carry out the reaction, with a stirring rate of 600 r / min.
[0128] (3) 24 g of allyltrimethylammonium chloride and 24 g of sodium methyl propylene sulfonate were added to 50 mL of water to obtain a solution.
[0129] (4) The reaction product obtained in step (2) and the solution obtained in step (3) are charged into a constant pressure dropping funnel and slowly added to a reaction bottle at a dropping speed of one drop per 3 seconds; 0.08 g of ammonium persulfate is added to 7 mL of water to obtain an ammonium persulfate solution; 0.04 g of sodium bisulfite is added to 3 mL of water to obtain an ammonium bisulfite solution; the ammonium persulfate solution is added dropwise to the reaction system at a dropping speed of one drop per 3 seconds, and the addition is completed within 3 minutes; after 5 minutes, the sodium bisulfite solution is added dropwise to the reaction system at a dropping speed of one drop per 3 seconds, and the addition is completed within 3 minutes to carry out the reaction, and the reaction is continued; after the reaction is completed, the reaction is naturally cooled to room temperature to obtain a transparent viscous substance.
[0130] (5) The transparent viscous substance obtained in step (5) is purified by anhydrous ethanol and then dried to obtain a white solid. The white powder after crushing is the salt-responsive hyperbranched polymer fluid loss reducer A3 of the present invention.
[0131] (6) 16 g of bentonite and 2.4 g of anhydrous sodium carbonate were added to 400 mL of water, stirred at high speed for 20 min, and cured at room temperature for 24 h to obtain a fresh water base slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A3 of the present invention was mixed with the fresh water base slurry and stirred at high speed for 20 min to obtain a test sample A3-1.
[0132] (7) 44 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A3 of the present invention was mixed with the saltwater slurry to obtain a test sample A3-2.
[0133] (8) 100 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A3 of the present invention was mixed with the saltwater slurry to obtain a test sample A3-3.
[0134] (9) 140 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A3 of the present invention was mixed with the saltwater slurry to obtain a test sample A3-4.
[0135] (10) Test sample A3-1, test sample A3-2, test sample A3-3 and test sample A3-4 obtained in step (6), step (7), step (8) and step (9) are respectively added into an aging tank and hot-rolled at 220°C for 16 hours to obtain test sample A3-5, test sample A3-6, test sample A3-7 and test sample A3-8, respectively.
[0136] Test samples A3-1, A3-2, A3-3, A3-4, A3-5, A3-6, A3-7 and A3-8 were subjected to apparent viscosity test, plastic viscosity test, dynamic shear force test, API filtration loss test and HTHP filtration loss test respectively. The results are as follows:
[0137] The apparent viscosity of the test sample A3-1 is 6.5 mPa·s, the plastic viscosity is 5 mPa·s, the dynamic shear force is 1.5 Pa, and the API filtration loss is 8.5 mL.
[0138] The apparent viscosity of the test sample A3-2 is 8 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 1 Pa, and the API filtration loss is 7.9 mL.
[0139] The apparent viscosity of the test sample A3-3 is 9.5 mPa·s, the plastic viscosity is 9 mPa·s, the dynamic shear force is 0.5 Pa, and the API filtration loss is 6.7 mL.
[0140] The apparent viscosity of the test sample A3-4 is 10 mPa·s, the plastic viscosity is 9 mPa·s, the dynamic shear force is 1 Pa, and the API filtration loss is 6.8 mL.
[0141] The apparent viscosity of the test sample A3-5 is 5.5 mPa·s, the plastic viscosity is 5 mPa·s, the dynamic shear force is 0.5 Pa, the API filtration loss is 8.7 mL, and the HTHP filtration loss is 18.4 mL.
[0142] The apparent viscosity of the test sample A3-6 is 7.5 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 0.5 Pa, the API filtration loss is 7.9 mL, and the HTHP filtration loss is 18.2 mL.
[0143] The apparent viscosity of the test sample A3-7 is 9 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 1 Pa, the API filtration loss is 6.9 mL, and the HTHP filtration loss is 17.8 mL.
[0144] The apparent viscosity of the test sample A3-8 is 10 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 2 Pa, the API filtration loss is 6.2 mL, and the HTHP filtration loss is 17.5 mL.
[0145] Example 4
[0146] (1) 20 g of acrylamide and 60 mL of water were added to a reactor. Under stirring, 1 g of pentaerythritol triallyl ether was added to the reaction device, nitrogen was introduced to react, and the stirrer speed was 500 r / min.
[0147] (2) Add 0.02 g of ammonium persulfate to 2 mL of water to obtain an ammonium persulfate solution. Add 0.01 g of ammonium bisulfite to 1 mL of water to obtain an ammonium bisulfite solution. Heat the reaction system obtained in step (1) to 35°C, introduce nitrogen for 30 min, then drop the ammonium persulfate solution into the reaction system, control the drop rate to one drop every 3 seconds, and complete the drop within 3 min; 5 min later, add the sodium bisulfite solution into the reaction system, control the drop rate to one drop every 3 seconds, and complete the drop within 3 min to carry out the reaction.
[0148] (3) 10 g of dimethyldiallylammonium chloride and 10 g of sodium 2-acrylamide-2-methylpropanesulfonate were added to 20 mL of water to obtain a solution.
[0149] (4) The reaction product obtained in step (2) and the solution obtained in step (3) are loaded into a constant pressure dropping funnel, and slowly added to a reaction bottle, with the dropping speed controlled at one drop per 3 seconds; 0.02 g of ammonium persulfate is added to 2 mL of water to obtain an ammonium persulfate solution; 0.01 g of sodium bisulfite is added to 1 mL of water to obtain an ammonium bisulfite solution; the ammonium persulfate solution is added dropwise to the reaction system, with the dropping speed controlled at one drop per 3 seconds, and the addition is completed within 3 minutes. After 5 minutes, the sodium bisulfite solution is added dropwise to the reaction system, with the dropping speed controlled at one drop per 3 seconds, and the addition is completed within 3 minutes to react. After the reaction is completed, the mixture is naturally cooled to room temperature to obtain a transparent viscous substance.
[0150] (5) The transparent viscous substance obtained in step (5) is purified by anhydrous ethanol and then dried to obtain a white solid. The white powder after crushing is the salt-responsive hyperbranched polymer fluid loss reducer A4 of the present invention.
[0151] (6) 16 g of bentonite and 2.4 g of anhydrous sodium carbonate were added to 400 mL of water, stirred at high speed for 20 min, and cured at room temperature for 24 h to obtain a freshwater base slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A4 of the present invention was mixed with the freshwater base slurry and stirred at high speed for 20 min to obtain a test sample A4-1.
[0152] (7) 44 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A4 of the present invention was mixed with the saltwater slurry to obtain a test sample A4-2.
[0153] (8) 100 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A4 of the present invention was mixed with the saltwater slurry to obtain a test sample A4-3.
[0154] (9) 140 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A4 of the present invention was mixed with the saltwater slurry to obtain a test sample A4-4.
[0155] (10) Test sample A4-1, test sample A4-2, test sample A4-3 and test sample A4-4 obtained in step (6), step (7), step (8) and step (9) are respectively added into an aging tank and hot-rolled at 220°C for 16 hours to obtain test sample A4-5, test sample A4-6, test sample A4-7 and test sample A4-8, respectively.
[0156] Test samples A4-1, A4-2, A4-3, A4-4, A4-5, A4-6, A4-7 and A4-8 were subjected to apparent viscosity test, plastic viscosity test, dynamic shear force test, API filtration loss test and HTHP filtration loss test respectively. The results are as follows:
[0157] The apparent viscosity of the test sample A4-1 is 5.5 mPa·s, the plastic viscosity is 4 mPa·s, the dynamic shear force is 1.5 Pa, and the API filtration loss is 8 mL.
[0158] The apparent viscosity of the test sample A4-2 is 7 mPa·s, the plastic viscosity is 6 mPa·s, the dynamic shear force is 1 Pa, and the API filtration loss is 7.6 mL.
[0159] The apparent viscosity of the test sample A4-3 is 8.5 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 1.5 Pa, and the API filtration loss is 6.5 mL.
[0160] The apparent viscosity of the test sample A4-4 is 9.5 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 1.5 Pa, and the API filtration loss is 6.2 mL.
[0161] The apparent viscosity of the test sample A4-5 is 4.5 mPa·s, the plastic viscosity is 4 mPa·s, the dynamic shear force is 0.5 Pa, the API filtration loss is 9.8 mL, and the HTHP filtration loss is 18.7 mL.
[0162] The apparent viscosity of the test sample A4-6 is 5 mPa·s, the plastic viscosity is 4 mPa·s, the dynamic shear force is 1 Pa, the API filtration loss is 8 mL, and the HTHP filtration loss is 17.8 mL.
[0163] The apparent viscosity of the test sample A4-7 is 7 mPa·s, the plastic viscosity is 6 mPa·s, the dynamic shear force is 1 Pa, the API filtration loss is 7.5 mL, and the HTHP filtration loss is 17.5 mL.
[0164] The apparent viscosity of the test sample A4-8 is 8 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 1 Pa, the API filtration loss is 7.2 mL, and the HTHP filtration loss is 18.4 mL.
[0165] Example 5
[0166] (1) 8 g of acrylamide, 8 g of methacrylamide, 8 g of N,N-dimethylacrylamide and 70 mL of water were added to a reactor. Under stirring, 2 g of triallyl carbinol was added to the reaction device, nitrogen was introduced to react, and the stirrer speed was 500 r / min.
[0167] (2) Add 0.05 g of ammonium persulfate to 5 mL of water to obtain an ammonium persulfate solution. Add 0.025 g of ammonium bisulfite to 2.5 mL of water to obtain an ammonium bisulfite solution. Heat the reaction system obtained in step (1) to 40°C, introduce nitrogen for 30 minutes, then drop the ammonium persulfate solution into the reaction system, control the drop rate to one drop every 3 seconds, and complete the drop within 3 minutes; 5 minutes later, add the sodium bisulfite solution into the reaction system, control the drop rate to one drop every 3 seconds, and complete the drop within 3 minutes to carry out the reaction.
[0168] (3) 12 g of (3-acrylamidopropyl)trimethylammonium chloride and 12 g of sodium styrene sulfonate were added to 25 mL of water to obtain a solution.
[0169] (4) The reaction product obtained in step (2) and the solution obtained in step (3) are loaded into a constant pressure dropping funnel, and slowly added to a reaction bottle, with the dropping speed controlled at one drop per 3 seconds; 0.05 g of ammonium persulfate is added to 5 mL of water to obtain an ammonium persulfate solution; 0.025 g of sodium bisulfite is added to 2.5 mL of water to obtain an ammonium bisulfite solution; the ammonium persulfate solution is added dropwise to the reaction system, with the dropping speed controlled at one drop per 3 seconds, and the addition is completed within 3 minutes. After 5 minutes, the sodium bisulfite solution is added dropwise to the reaction system, with the dropping speed controlled at one drop per 3 seconds, and the addition is completed within 3 minutes to react. After the reaction is completed, the mixture is naturally cooled to room temperature to obtain a transparent viscous substance.
[0170] (5) The transparent viscous substance obtained in step (5) is purified by anhydrous ethanol and then dried to obtain a white solid. The white powder after crushing is the salt-responsive hyperbranched polymer fluid loss reducer A5 of the present invention.
[0171] (6) 16 g of bentonite and 2.4 g of anhydrous sodium carbonate were added to 400 mL of water, stirred at high speed for 20 min, and cured at room temperature for 24 h to obtain a fresh water base slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A5 of the present invention was mixed with the fresh water base slurry and stirred at high speed for 20 min to obtain a test sample A5-1.
[0172] (7) 44 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A5 of the present invention was mixed with the saltwater slurry to obtain a test sample A5-2.
[0173] (8) 100 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A5 of the present invention was mixed with the saltwater slurry to obtain a test sample A5-3.
[0174] (9) 140 g of NaCl was added to the freshwater slurry obtained in step (6), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A5 of the present invention was mixed with the saltwater slurry to obtain a test sample A5-4.
[0175] (10) Test sample A5-1, test sample A5-2, test sample A5-3 and test sample A5-4 obtained in step (6), step (7), step (8) and step (9) are respectively added into an aging tank and hot-rolled at 220°C for 16 hours to obtain test sample A5-5, test sample A5-6, test sample A5-7 and test sample A5-8, respectively.
[0176] Test samples A5-1, A5-2, A5-3, A5-4, A5-5, A5-6, A5-7 and A5-8 were subjected to apparent viscosity test, plastic viscosity test, dynamic shear force test, API filtration loss test and HTHP filtration loss test respectively. The results are as follows:
[0177] The apparent viscosity of the test sample A5-1 is 5.5 mPa·s, the plastic viscosity is 4 mPa·s, the dynamic shear force is 1.5 Pa, and the API filtration loss is 8.8 mL.
[0178] The apparent viscosity of the test sample A5-2 is 7 mPa·s, the plastic viscosity is 5 mPa·s, the dynamic shear force is 2 Pa, and the API filtration loss is 7.2 mL.
[0179] The apparent viscosity of the test sample A5-3 is 8.5 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 1.5 Pa, and the API filtration loss is 6.4 mL.
[0180] The apparent viscosity of the test sample A5-4 is 10 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 3 Pa, and the API filtration loss is 6.8 mL.
[0181] The apparent viscosity of the test sample A5-5 is 5 mPa·s, the plastic viscosity is 4 mPa·s, the dynamic shear force is 1 Pa, the API filtration loss is 7.8 mL, and the HTHP filtration loss is 19.2 mL.
[0182] The apparent viscosity of the test sample A5-6 is 6 mPa·s, the plastic viscosity is 5 mPa·s, the dynamic shear force is 1 Pa, the API filtration loss is 7.6 mL, and the HTHP filtration loss is 18.9 mL.
[0183] The apparent viscosity of the test sample A5-7 is 7.5 mPa·s, the plastic viscosity is 6 mPa·s, the dynamic shear force is 1.5 Pa, the API filtration loss is 7.2 mL, and the HTHP filtration loss is 19.6 mL.
[0184] The apparent viscosity of the test sample A5-8 is 9.5 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 1.5 Pa, the API filtration loss is 7.2 mL, and the HTHP filtration loss is 20.2 mL.
[0185] Example 6
[0186] (1) According to the method of Example 1, the salt-responsive hyperbranched polymer fluid loss reducer A1 of the present invention was prepared.
[0187] (2) Add 16 g of bentonite and 2.4 g of anhydrous sodium carbonate to 400 mL of water, stir at high speed for 20 min, and cure at room temperature for 24 h to obtain a fresh water base slurry.
[0188] (3) 4 g of CaCl2 was added to the freshwater slurry obtained in step (2), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A1 of the present invention was mixed with the saltwater slurry to obtain a test sample A6-1.
[0189] (4) Add 20 g of CaCl2 to the freshwater slurry obtained in step (2), stir at high speed for 20 min, and stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A1 of the present invention was mixed with the saltwater slurry to obtain a test sample A6-2.
[0190] (5) 44 g of CaCl2 was added to the freshwater slurry obtained in step (2), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A1 of the present invention was mixed with the saltwater slurry to obtain a test sample A6-3.
[0191] (6) Test sample A6-1, test sample A6-2 and test sample A6-3 obtained in step (3), step (4) and step (5) are added into aging tanks respectively, and hot-rolled at 220°C for 16 hours to obtain test sample A6-4, test sample A6-5 and test sample A6-6 respectively.
[0192] Test samples A6-1, A6-2, A6-3, A6-4, A6-5 and A6-6 were subjected to apparent viscosity test, plastic viscosity test, dynamic shear force test, API filtration loss test and HTHP filtration loss test respectively. The results are as follows:
[0193] The apparent viscosity of the test sample A6-1 is 7 mPa·s, the plastic viscosity is 5 mPa·s, the dynamic shear force is 2 Pa, and the API filtration loss is 7.4 mL.
[0194] The apparent viscosity of the test sample A6-2 is 9 mPa·s, the plastic viscosity is 6 mPa·s, the dynamic shear force is 3 Pa, and the API filtration loss is 7.2 mL.
[0195] The apparent viscosity of the test sample A6-3 is 11.5 mPa·s, the plastic viscosity is 9 mPa·s, the dynamic shear force is 2.5 Pa, and the API filtration loss is 6.5 mL.
[0196] The apparent viscosity of the test sample A6-4 is 6 mPa·s, the plastic viscosity is 4 mPa·s, the dynamic shear force is 2 Pa, the API filtration loss is 7.6 mL, and the HTHP filtration loss is 17 mL.
[0197] The apparent viscosity of the test sample A6-5 is 8.5 mPa·s, the plastic viscosity is 6 mPa·s, the dynamic shear force is 2.5 Pa, the API filtration loss is 7.5 mL, and the HTHP filtration loss is 18.6 mL.
[0198] The apparent viscosity of the test sample A6-6 is 10 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 2 Pa, the API filtration loss is 6.8 mL, and the HTHP filtration loss is 19.4 mL.
[0199] Example 7
[0200] (1) According to the method of Example 4, the salt-responsive hyperbranched polymer fluid loss reducer A4 of the present invention was prepared.
[0201] (2) Add 16 g of bentonite and 2.4 g of anhydrous sodium carbonate to 400 mL of water, stir at high speed for 20 min, and cure at room temperature for 24 h to obtain a fresh water base slurry.
[0202] (3) Add 4 g of CaCl2 to the freshwater slurry obtained in step (2), stir at high speed for 20 min, and stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A4 of the present invention was mixed with the saltwater slurry to obtain a test sample A7-1.
[0203] (4) Add 20 g of CaCl2 to the freshwater slurry obtained in step (2), stir at high speed for 20 min, and stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A4 of the present invention was mixed with the saltwater slurry to obtain a test sample A7-2.
[0204] (5) Add 44 g of CaCl2 to the freshwater slurry obtained in step (2), stir at high speed for 20 min, and stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A4 of the present invention was mixed with the saltwater slurry to obtain a test sample A7-3.
[0205] (6) Test sample A7-1, test sample A7-2 and test sample A7-3 obtained in step (3), step (4) and step (5) are respectively added into an aging tank and hot-rolled at 220° C. for 16 hours to obtain test sample A7-4, test sample A7-5 and test sample A7-6, respectively.
[0206] Test samples A7-1, A7-2, A7-3, A7-4, A7-5 and A7-6 were subjected to apparent viscosity test, plastic viscosity test, dynamic shear force test, API filtration loss test and HTHP filtration loss test respectively. The results are as follows:
[0207] The apparent viscosity of the test sample A7-1 is 6 mPa·s, the plastic viscosity is 5 mPa·s, the dynamic shear force is 1 Pa, and the API filtration loss is 7.8 mL.
[0208] The apparent viscosity of the test sample A7-2 is 8.5 mPa·s, the plastic viscosity is 6 mPa·s, the dynamic shear force is 2.5 Pa, and the API filtration loss is 7.4 mL.
[0209] The apparent viscosity of the test sample A7-3 is 11 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 4 Pa, and the API filtration loss is 7.8 mL.
[0210] The apparent viscosity of the test sample A7-4 is 5 mPa·s, the plastic viscosity is 4 mPa·s, the dynamic shear force is 1 Pa, the API filtration loss is 8.5 mL, and the HTHP filtration loss is 18 mL.
[0211] The apparent viscosity of the test sample A7-5 is 7.5 mPa·s, the plastic viscosity is 5 mPa·s, the dynamic shear force is 2.5 Pa, the API filtration loss is 8 mL, and the HTHP filtration loss is 17.4 mL.
[0212] The apparent viscosity of the test sample A7-6 is 11 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 3 Pa, the API filtration loss is 6.8 mL, and the HTHP filtration loss is 16.8 mL.
[0213] Example 8
[0214] (1) According to the method of Example 5, the salt-responsive hyperbranched polymer fluid loss reducer A5 of the present invention was prepared.
[0215] (2) Add 16 g of bentonite and 2.4 g of anhydrous sodium carbonate to 400 mL of water, stir at high speed for 20 min, and cure at room temperature for 24 h to obtain a fresh water base slurry.
[0216] (3) 4 g of CaCl2 was added to the freshwater slurry obtained in step (2), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A5 of the present invention was mixed with the saltwater slurry to obtain a test sample A8-1.
[0217] (4) Add 20 g of CaCl2 to the freshwater slurry obtained in step (2), stir at high speed for 20 min, and stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A5 of the present invention was mixed with the saltwater slurry to obtain a test sample A8-2.
[0218] (5) 44 g of CaCl2 was added to the freshwater slurry obtained in step (2), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of the salt-responsive hyperbranched polymer fluid loss reducer A5 of the present invention was mixed with the saltwater slurry to obtain a test sample A8-3.
[0219] (6) Test sample A8-1, test sample A8-2 and test sample A8-3 obtained in step (3), step (4) and step (5) are respectively added into an aging tank and hot-rolled at 220°C for 16 hours to obtain test sample A8-4, test sample A8-5 and test sample A8-6, respectively.
[0220] Test samples A8-1, A8-2, A8-3, A8-4, A8-5 and A8-6 were subjected to apparent viscosity test, plastic viscosity test, dynamic shear force test, API filtration loss test and HTHP filtration loss test respectively. The results are as follows:
[0221] The apparent viscosity of the test sample A8-1 is 6.5 mPa·s, the plastic viscosity is 5 mPa·s, the dynamic shear force is 1.5 Pa, and the API filtration loss is 7.8 mL.
[0222] The apparent viscosity of the test sample A8-2 is 8.5 mPa·s, the plastic viscosity is 6 mPa·s, the dynamic shear force is 2.5 Pa, and the API filtration loss is 7.2 mL.
[0223] The apparent viscosity of the test sample A8-3 is 12 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 4 Pa, and the API filtration loss is 7 mL.
[0224] The apparent viscosity of the test sample A8-4 is 6 mPa·s, the plastic viscosity is 5 mPa·s, the dynamic shear force is 1 Pa, the API filtration loss is 8.4 mL, and the HTHP filtration loss is 17.2 mL.
[0225] The apparent viscosity of the test sample A8-5 is 8 mPa·s, the plastic viscosity is 6 mPa·s, the dynamic shear force is 2 Pa, the API filtration loss is 7.9 mL, and the HTHP filtration loss is 18 mL.
[0226] The apparent viscosity of the test sample A8-6 is 10.5 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 2.5 Pa, the API filtration loss is 7.2 mL, and the HTHP filtration loss is 18.5 mL.
[0227] Comparative Example 1
[0228] According to the method of the prior art (CN115850570A), a fluid loss reducer for drilling fluid is prepared, and the method and steps are as follows:
[0229] (1) Add 2 g of span80, 2 g of tween60 and 60 g of white oil into a mixing device and stir at a stirring speed of 1500 r / min for 30 min to obtain an oil phase solvent.
[0230] (2) 2 g of tripentaerythritol octaallyl ether, 20 g of methanol and 30 g of water were added into a mixing device and mixed uniformly to obtain a solution.
[0231] (3) The solution obtained in step (2) and the oil phase solvent in step (1) are added to a mixing device for stirring at a stirring speed of 1500 r / min, and then emulsified to obtain an emulsion.
[0232] (4) The emulsion obtained in step (3) was deoxygenated with nitrogen for 30 minutes, heated to 75° C., and then a mixture of 0.02 g of azobisisobutyronitrile and 2 mL of methanol was added dropwise to the emulsion within 5 minutes, and the reaction was carried out for 16 hours.
[0233] (5) 8 g of 2-ethyl methacrylate sodium salt, 16 g of hydroxymethylstyrene, 4 g of N,N-methylenebisacrylamide, 24 g of dimethylallylamide and 70 g of water were added into a mixing device and mixed uniformly to obtain a solution.
[0234] (6) After the temperature of the reaction product obtained in step (4) drops to 60° C., the solution obtained in step (5) is placed in a constant pressure dropping funnel and slowly added to the emulsion obtained in step (3), with the dropping speed controlled at one drop per 3 seconds; 0.01 g of 2,2-azobis(2-methylpropylimidamide) dihydrochloride is added to 1 mL of water and added to the reaction system to continue the reaction; the reaction is completed after 4 hours of reaction, and the mixture is naturally cooled to room temperature to obtain a fluid loss reducer D1.
[0235] (7) Add 16 g of bentonite and 2.4 g of anhydrous sodium carbonate to 400 mL of water, stir at high speed for 20 min, and cure at room temperature for 24 h to obtain a freshwater base slurry. Mix 4 g of fluid loss agent D1 with the freshwater base slurry and stir at high speed for 20 min to obtain test sample D1-1.
[0236] (8) Add 44 g of NaCl to the freshwater slurry obtained in step (7), stir at high speed for 20 min, and stand at room temperature for 24 h to obtain a saltwater slurry. Mix 4 g of fluid loss reducer D1 with the saltwater slurry to obtain test sample D1-2.
[0237] (9) 100 g of NaCl was added to the freshwater slurry obtained in step (7), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of fluid loss reducer D1 was mixed with the saltwater slurry to obtain test sample D1-3.
[0238] (10) 140 g of NaCl was added to the freshwater slurry obtained in step (7), stirred at high speed for 20 min, and allowed to stand at room temperature for 24 h to obtain a saltwater slurry. 4 g of fluid loss reducer D1 was mixed with the saltwater slurry to obtain test sample D1-4.
[0239] (11) Test sample D1-1, test sample D1-2, test sample D1-3 and test sample D1-4 obtained in step (7), step (8), step (9) and step (10) are respectively added into an aging tank and hot-rolled at 220°C for 16 hours to obtain test sample D1-5, test sample D1-6, test sample D1-7 and test sample D1-8, respectively.
[0240] Test samples D1-1, D1-2, D1-3, D1-4, D1-5, D1-6, D1-7 and D1-8 were subjected to apparent viscosity test, plastic viscosity test, dynamic shear force test, API filtration loss test and HTHP filtration loss test respectively. The results are as follows:
[0241] The apparent viscosity of the test sample D1-1 is 9 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 2 Pa, and the API filtration loss is 9.2 mL.
[0242] The apparent viscosity of the test sample D1-2 is 8 mPa·s, the plastic viscosity is 6 mPa·s, the dynamic shear force is 2 Pa, and the API filtration loss is 8.2 mL.
[0243] The apparent viscosity of the test sample D1-3 is 9 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 1 Pa, and the API filtration loss is 7.2 mL.
[0244] The apparent viscosity of the test sample D1-4 is 8.5 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 1.5 Pa, and the API filtration loss is 6.8 mL.
[0245] The apparent viscosity of the test sample D1-5 is 9.5 mPa·s, the plastic viscosity is 9 mPa·s, the dynamic shear force is 0.5 Pa, the API filtration loss is 9.5 mL, and the HTHP filtration loss is 21.5 mL.
[0246] The apparent viscosity of the test sample D1-6 is 8.5 mPa·s, the plastic viscosity is 8 mPa·s, the dynamic shear force is 0.5 Pa, the API filtration loss is 8.4 mL, and the HTHP filtration loss is 18.8 mL.
[0247] The apparent viscosity of the test sample D1-7 is 9 mPa·s, the plastic viscosity is 7 mPa·s, the dynamic shear force is 2 Pa, the API filtration loss is 8 mL, and the HTHP filtration loss is 19.2 mL.
[0248] The apparent viscosity of the test sample D1-8 is 8.5 mPa·s, the plastic viscosity is 6 mPa·s, the dynamic shear force is 2.5 Pa, the API filtration loss is 6.6 mL, and the HTHP filtration loss is 17 mL.
[0249] Comparative Example 2
[0250] (1) Prepare filtrate reducer D1 according to the method of Comparative Example 1.
[0251] (2) Add 16 g of bentonite and 2.4 g of anhydrous sodium carbonate to 400 mL of water, stir at high speed for 20 min, and cure at room temperature for 24 h to obtain a fresh water base slurry.
[0252] (3) Add 4 g of CaCl2 to the freshwater slurry obtained in step (2), stir at high speed for 20 min, and stand at room temperature for 24 h to obtain a saltwater slurry. Mix 4 g of fluid loss reducer D1 with the saltwater slurry to obtain test sample D2-1.
[0253] (4) Add 20 g of CaCl2 to the freshwater slurry obtained in step (2), stir at high speed for 20 min, and stand at room temperature for 24 h to obtain a saltwater slurry. Mix 4 g of fluid loss reducer D1 with the saltwater slurry to obtain test sample D2-2.
[0254] (5) Add 44 g of CaCl2 to the freshwater slurry obtained in step (2), stir at high speed for 20 min, and stand at room temperature for 24 h to obtain a saltwater slurry. Mix 4 g of fluid loss reducer D1 with the saltwater slurry to obtain test sample D2-3.
[0255] (6) Test sample D2-1, test sample D2-2 and test sample D2-3 obtained in step (7), step (8) and step (9) are respectively added into an aging tank and hot-rolled at 220°C for 16 hours to obtain test sample D2-4, test sample D2-5 and test sample D2-6, respectively.
[0256] Test samples D2-1, D2-2, D2-3, D2-4, D2-5 and D2-6 were subjected to apparent viscosity test, plastic viscosity test, dynamic shear force test, API filtration loss test and HTHP filtration loss test respectively. The results are as follows:
[0257] The apparent viscosity of the test sample D2-1 is 4.5 mPa·s, the plastic viscosity is 4 mPa·s, the dynamic shear force is 0.5 Pa, and the API filtration loss is 18 mL.
[0258] The apparent viscosity of the test sample D2-2 is 3.5 mPa·s, the plastic viscosity is 2.5 mPa·s, the dynamic shear force is 1 Pa, and the API filtration loss is 51.5 mL.
[0259] The apparent viscosity of the test sample D2-3 is 3 mPa·s, the plastic viscosity is 2 mPa·s, the dynamic shear force is 1 Pa, and the API filtration loss is 109 mL.
[0260] The apparent viscosity of the test sample D2-4 is 2 mPa·s, the plastic viscosity is 1 mPa·s, the dynamic shear force is 1 Pa, the API filtration loss is 23.5 mL, and the HTHP filtration loss is 52.5.
[0261] The apparent viscosity of the test sample D2-5 is 2 mPa·s, the plastic viscosity is 1 mPa·s, and the dynamic shear force is 1 Pa.
[0262] The apparent viscosity of the test sample D2-6 is 1.5 mPa·s, the plastic viscosity is 1 mPa·s, and the dynamic shear force is 0.5 Pa.
[0263] The corresponding operating conditions of the above embodiments and comparative examples and the performance parameters of the fluid loss reducer samples are shown in Table 1 below.
[0264] Table 1
[0265]
[0266]
[0267]
[0268]
[0269] It can be seen from the results in Table 1 that the salt-responsive hyperbranched polymer fluid loss reducer prepared according to the method described in the present invention has significantly better fluid loss reduction performance.
[0270] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A salt-responsive hyperbranched polymer fluid loss reducer, characterized in that: The salt-responsive hyperbranched polymer fluid loss additive comprises: The first structural unit is provided by an unsaturated amide water-soluble monomer; The second structural unit is provided by an unsaturated cationic water-soluble monomer; The third structural unit is provided by an unsaturated anionic water-soluble monomer; The fourth structural unit is provided by a polyene monomer; Wherein, the weight average molecular weight of the salt-responsive hyperbranched polymer fluid loss reducer is 20,000 to 100,000.
2. The salt-responsive hyperbranched polymer fluid loss reducer according to claim 1, characterized in that The weight ratio of the first structural unit, the second structural unit, the third structural unit and the fourth structural unit is (3-30):(1.6-20):(1.6-20):1, preferably (5-15):(3-8):(3-8):
1.
3. The salt-responsive hyperbranched polymer fluid loss reducer according to claim 1 or 2, characterized in that: The unsaturated amide water-soluble monomer is at least one of acrylamide, N-isopropylacrylamide, methacrylamide and N,N-dimethylacrylamide; and / or The unsaturated cationic water-soluble monomer is at least one of dimethyldiallylammonium chloride, (3-acrylamidopropyl)trimethylammonium chloride, methacryloyloxyethyltrimethylammonium chloride and allyltrimethylammonium chloride; and / or The unsaturated anionic water-soluble monomer is at least one of sodium 2-acrylamide-2-methylpropane sulfonate, sodium methacrylate sulfonate, sodium allyl sulfonate and sodium styrene sulfonate; and / or The polyolefin monomer is at least one of pentaerythritol triallyl ether, trimethylolpropane triallyl ether, triallylamine and triallylcarbinol.
4. A method for preparing a salt-responsive hyperbranched polymer fluid loss reducer, characterized in that: The method comprises the following steps: (1) mixing an unsaturated amide water-soluble monomer with water to obtain a first solution; (2) reacting the first solution obtained in step (1) with a polyene monomer in the presence of a first initiator under an inert atmosphere; (3) mixing an unsaturated cationic water-soluble monomer and an unsaturated anionic water-soluble monomer with water to obtain a second solution; (4) subjecting the second solution obtained in step (3) to a secondary reaction with the reaction product obtained in step (2) in the presence of a second initiator.
5. The method according to claim 4, characterized in that The weight ratio of the total amount of the unsaturated amide water-soluble monomer, the unsaturated cationic water-soluble monomer, the unsaturated anionic water-soluble monomer, the polyolefin monomer, the first initiator and the second initiator to water is (3-30): (1.6-20): (1.6-20): 1: (0.01-0.2): (14-200), preferably (5-15): (3-8): (3-8): 1: (0.05-0.15): (20-180).
6. The method according to claim 4 or 5, characterized in that: The unsaturated amide water-soluble monomer is at least one of acrylamide, N-isopropylacrylamide, methacrylamide and N,N-dimethylacrylamide; and / or The unsaturated cationic water-soluble monomer is at least one of dimethyldiallylammonium chloride, (3-acrylamidopropyl)trimethylammonium chloride, methacryloyloxyethyltrimethylammonium chloride and allyltrimethylammonium chloride; and / or The unsaturated anionic water-soluble monomer is at least one of sodium 2-acrylamide-2-methylpropane sulfonate, sodium methacrylate sulfonate, sodium allyl sulfonate and sodium styrene sulfonate; and / or The polyolefin monomer is at least one of pentaerythritol triallyl ether, trimethylolpropane triallyl ether, triallylamine and triallylcarbinol.
7. The method according to claim 4, characterized in that In step (1), the mass ratio of the unsaturated amide water-soluble monomer to water is 1:(1-5), preferably 1:(2-4).
8. The method according to claim 4, characterized in that In step (2), the first initiator is used in the form of an aqueous solution, and the concentration of the aqueous solution of the first initiator is 0.005-0.02 g / mL, preferably 0.006-0.015 g / mL.
9. The method according to claim 4 or 8, characterized in that: In step (2), the primary reaction is carried out under stirring, and the conditions of the primary reaction include: a temperature of 35-45° C. and a stirring speed of 300-1000 r / min.
10. The method according to claim 4, characterized in that In step (3), the mass ratio of the total amount of the unsaturated cationic water-soluble monomer and the unsaturated anionic water-soluble monomer to water is 1:(0.5-1.5), preferably 1:(0.8-1.2).
11. The method according to claim 4, characterized in that The first initiator and the second initiator are each ammonium persulfate and / or sodium bisulfite.
12. The method according to claim 4, characterized in that In step (4), the secondary reaction time is 2-3 hours.
13. A drilling fluid, characterized in that: The drilling fluid contains the salt-responsive hyperbranched polymer fluid loss reducer according to any one of claims 1 to 3.
Citation Information
Patent Citations
Hyperbranched polymer microsphere filtrate reducer as well as preparation method and application thereof
CN115850570A